Polymorphism of a low penetrance cancer suseptible gene, STK15, in colorectal cancer - Lai, Tianxin (2012)
STK15 is a serine/theorine kinase involved in cell cycle regulation. This low penetrance gene attributes to many cancers. This project aims to study the polymorhisms of STK15 on the occurrence of colorectal cancer. Two polymorphism sites in STK15 were studied in this study, nucleotide change at 91 from T→A causes amino acid Phe31Ile substitution and G/A polymorphism at nucleotide 169 encode valine → isoleucine (V57I) at amino acid position 57. We genotyped 120 patients with colorectal cancer at different stages and 1116 healthy controls for STK15 polymorphisms. DNA were extracted from peripheral blood using Flexigene DNA kit (Qiagen). Genotyping of the Phe31Ile and Val57Ile polymorphism sites were analyzed by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism using ApoI and BstUI restriction enzymes, respectively. These polymorphisms were further confirmed by DNA sequencing. Statistical analyses were done using Statistical Package for Social Science, SPSS version 17.0. The genotype of the study subjects were analysed according to three genetic models-dominant, codominant and recessive. Sequencing results confirmed a transversion of T-to-A in Phe31Ile polymorphism while Val57Ile polymorphism has a transversion of G-to-A. Using the dominant model, the ORs for Phe/Ile+Ile/Ile genotype of Phe31Ile polymorphism was 1.014 (95% CI=0.591-1.739) when compared with Phe/Phe genotype while the OR for Val/Ile+Ile/Ile genotypes of Val57Ile polymorphism was 1.034 (95% CI=0.685-1.560) when compared with Val/Val genotype. For codominant genetic model, homozygous Ile/Ile and heterozygous Phe/Ile genotypes in Phe31Ile polymorphism does not increased the risk of colorectal cancer [Ile/Ile; OR=0.889, 95% CI=0.488-1.622, Phe/Ile; OR=1.104, 95% CI=0.629-1.937]. Moreover, homozygous Ile/Ile and Val/Ile in Val57Ile polymorphism also do not show association with the risk to colorectal cancer [Ile/Ile; OR=1.497, 95% CI=0.509-4.405, Val/Ile; OR=0.982, 95% CI=0.640-1.506]. By using recessive model, the OR calculated for Ile/Ile genotype when compare with Phe/Ile+Phe/Phe genotypes and with Val/Val+Val/Ile genotypes were 0.823 (95% CI=0.550-1.232) and 0.719 (95% CI=0.247-2.091), respectively. Using the Phe/Phe+Val/Val as reference, the OR and 95% CI was calculated for the combined genotype (TT+GA; OR=1.514, 95% CI=0.472-4.848, TT+AA; OR=3.733, 95% CI=0.895-15.572, TA+GG; OR=1.734, 95% CI=0.661-4.545, TA+GA; OR=1.570, 95% CI=0.577-4.271, AA+GG; OR=1.375, 95% CI=0.523-3.614). None of the results showed statistically significance association with colorectal cancer. However, STK15 was over expressed 2.1 fold in cancerous cells compared to normal healthy cells when real-time PCR was performed using Human TATA-box binding protein as endogenous control. STK15 do not show significant association with colorectal cancer because as being a low penentrance gene, STK15 might moderately affect the risk of colorectal cancer. A broader study including other factors such as diet, life-style and other penetrance genes that might work significantly together with colorectal cancer will be able to confirm the combination of STK15 and others factors in affecting the risk of colorectal cancer.